Break the Eclectic Choice: Can Green Credit Policy Restraint the Polluting Firms’ Financialization? Evidence From China - Xi Gu; Sijia Qiao (SAGE Open)
The innovative use of green credit policy for financial regulation in environmental governance is a significant effort to balance environmental preservation and economic growth. The objective of this paper is to study the effect of green credit on the polluting firms’ eclectic business strategy, which is financialization, and the related mechanisms. Based on the sample of Chinese public firms from 2008 to 2019, we employ the DID model constructed by the Green Credit Guidelines promulgated in 2012 to investigate the causality between green credit policy and firms’ financialization. The results of theoretical and empirical studies show that the green credit policy helps to mitigate the financialization of heavy polluters compared to non-heavily polluting firms, thereby realizing the optimal allocation of financial resources. The mechanism test indicates that green credit policy has a suppressive effect on the financialization level of heavily polluting firms, mainly through promoting green innovation while reducing excess cash and banks’ credit willingness. The heterogeneity test further indicates that green credit policy is more pronounced in SOEs, strong environmental regulation enforcement regions and higher market competition industries. Our study confirms the effectiveness of green credit policies from the perspective of firms’ business strategy, which not only provides empirical evidence for the evaluation of green credit policy effects, but also sheds lights on the green transformation and sustainable development of heavily polluting firms.